2007
DOI: 10.1016/j.jad.2007.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of bipolar I disorder among adults with primary youth‐onset anxiety disorders

Abstract: Objectives-It is of potentially great public health importance to determine whether youth-onset anxiety disorders are associated with increased prevalence of subsequent bipolar I disorder (BD) among adults, and to identify risk factors for BD in this population. Methods-The 2001-2002National Epidemiologic Survey on Alcohol and Related Conditions was used to identify respondents with social phobia, panic disorder, or generalized anxiety disorder that onset in youth (<19 years) and was not preceded by a major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…On average, the onset of anxiety disorders preceded the onset of BP in individuals with both disorders and supports the idea that anxiety disorders could be a risk factor for subsequent development of BP (Goldstein & Levitt, 2007). Interestingly, recent studies found that offspring of parents with BP had higher rates of anxiety disorders than offspring of control parents suggesting that anxiety may be a precursor of BP among BP offspring (Birmaher et al, 2009; Goldstein et al).…”
Section: Discussionsupporting
confidence: 77%
“…On average, the onset of anxiety disorders preceded the onset of BP in individuals with both disorders and supports the idea that anxiety disorders could be a risk factor for subsequent development of BP (Goldstein & Levitt, 2007). Interestingly, recent studies found that offspring of parents with BP had higher rates of anxiety disorders than offspring of control parents suggesting that anxiety may be a precursor of BP among BP offspring (Birmaher et al, 2009; Goldstein et al).…”
Section: Discussionsupporting
confidence: 77%
“…There were no differences in the rates of other anxiety disorders, but the base rate of these disorders was low. Other studies of high risk for BP and studies of adults and youth with BP have also reported high rates of anxiety disorders 7,9,67-73. Also, high rates of anxiety disorders have been consistently observed in adults with early-onset BP when compared with adults with late-onset BP,1,70,71 and anxiety disorders appear to be associated with increased risk of developing BP during adulthood 44,74,75.…”
Section: Commentmentioning
confidence: 89%
“…Duffy and colleagues found that 30% of offspring of parents with BP who initially manifested sleep or anxiety disorders went on to develop BP 52. Retrospective studies indicate that childhood anxiety disorders and ODD/CD are more common among adults with BP compared to controls53, and youth-onset anxiety disorders have been associated with elevated rates of BP in adulthood 54. Previous studies have found starkly contradictory findings regarding ADHD.…”
Section: Discussionmentioning
confidence: 99%